2013
DOI: 10.1016/j.abb.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitroxyl (HNO) on H2O2 metabolism and possible mechanisms of HNO signaling

Abstract: Nitroxyl (HNO) possesses unique and potentially important biological/physiological activity that is currently mechanistically ill-defined. Previous work has shown that the likely biological targets for HNO are thiol proteins, oxidized metalloproteins (i.e. ferric heme proteins) and, most likely, selenoproteins. Interestingly, these are the same classes of proteins that interact with H2O2. In fact, these classes of proteins not only react with H2O2, and thus potentially responsible for the signaling actions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…110,156158 Reactions of HNO with the proteins that control hydrogen peroxide degradation reveals a “cross-talk” between HNO and hydrogen peroxide that may define new redox based signaling or gene expression pathways. 159 The combination of the advances in HNO detection and donation with these emerging areas highlights the enormous potential of these new chemical biology tools to understanding HNO’s actions in biology, physiology and medicine.…”
Section: Resultsmentioning
confidence: 99%
“…110,156158 Reactions of HNO with the proteins that control hydrogen peroxide degradation reveals a “cross-talk” between HNO and hydrogen peroxide that may define new redox based signaling or gene expression pathways. 159 The combination of the advances in HNO detection and donation with these emerging areas highlights the enormous potential of these new chemical biology tools to understanding HNO’s actions in biology, physiology and medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, only a few studies have examined the interaction between HNO and a selenoprotein. One study examined the ability for HNO to inhibit the selenoprotein glutathione peroxidase (GPx) [28] and reports that HNO was capable of inhibiting the activity of purified GPx under both aerobic and anaerobic conditions, with slightly more inhibition observed under aerobic conditions. Moreover, approximately 50% of the inhibition of GPx by HNO could not be reversed by the thiol reductant DTT, alluding to a significant population of an irreversibly modified adduct.…”
Section: Hno Chemistrymentioning
confidence: 99%
“…Also, since both H 2 O 2 and HNO presumably signal via electrophilic chemistry with thiols, there is a possibility that their signaling pathways are similar. Indeed, Jackson and coworkers [28] examined the relationship between H 2 O 2 and HNO and found that HNO was capable of increasing cellular levels of H 2 O 2 . Moreover, a comparison of the effects of H 2 O 2 and HNO on T-cell activation (a process reported to be regulated by H 2 O 2 ) found that they had identical signaling profiles.…”
Section: Hno Signaling/biological Activitymentioning
confidence: 99%
“…For the negative effects, in the case of Isoniazid this can be explained by the known inhibitory deleterious effect of HNO on heme proteins like catalase (the product of katG), necessary for activation of the pro-drug to its active form [24]. On the other hand, for Ethambutol it is still unclear the reason of the antagonism observed in this work and further studies are needed.…”
Section: Discussionmentioning
confidence: 81%